Antifungal activity of selected sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines using modified SPOTi assay - MARY GRACE EREGUERO; MARY ANNE CORDERO; RODELYN DALAYAP; SHARON ROSE TABUGO (Society for Indonesian Biodiversity, 2022)
Abstract. Ereguero MG, Cordero MA, Dalayap R, Tabugo SR. 2022. Antifungal activity of selected sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines using modified SPOTi assay. Biodiversitas 23: 6049-6055. Marine organisms have become essential candidates for discovering novel compounds that can be medically and commercially important. They are believed to yield novel compounds with unique chemical structures and significant biological activities since they managed to survive a milieu of pathogenic microorganisms and essential predators. The quest against fungal infections has been challenging due to acquired resistance to commercially available drugs hence, novel sources to treat infectious diseases caused by fungi have been investigated. Sea cucumbers have been recognized in Asian countries as a rich food source. Apart from that, they have also been studied for their medicinal properties. This study aimed to evaluate the antifungal activity of the selected sea cucumber species found in Brgy. Sugod, Tukuran, Zamboanga del Sur, Mindanao, Philippines using the modified SPOTi assay. Methanol: ethyl acetate crude extracts of Holothuria scabra, Stichopus sp., and Holothuria atra were tested for their antifungal activity against Aspergillus niger and Candida tropicalis. A 96-well plate assay was used, and the growth of fungi was assessed visually for up to 72hrs. The concentration resulting in ‘no fungal growth’ was observed and taken as the Minimum Inhibitory Concentration (MIC) value. The average MIC was calculated. Results showed that sea cucumber crude extracts have MIC values of 0.0333-0.1 mg/mL. Tukey’s posthoc test confirmed that the antifungal activity of the sea cucumber extracts was comparable to the positive control Fluconazole (p>0.05). The present study revealed a potentially effective natural antifungal agent from sea cucumbers.